2016
DOI: 10.1039/c6bm00079g
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer mediated clustering of bacteria: improved aggregation and evaluation of bacterial response and viability

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…We and others have previously observed that cationic polymers and dendrimers can, under certain conditions, trigger bioluminescence in the marine bacterium V. harveyi , suggesting they may induce or enhance quorum sensing. 7 , 8 , 10 , 11 In a more recent study where we extended this work to the human pathogen V. cholerae , we observed that polymer-mediated clustering led to enhanced deposition of biomass and extracellular DNA, whereas it interfered with the induction of virulence genes in an infection model. 12 Because virulence and biofilm production are both regulated by quorum sensing but are usually both regulated concurrently, the goal of this study was to test whether cationic polymers would trigger quorum sensing in V. cholerae and how this would affect downstream transcription of biofilm genes.…”
Section: Discussionmentioning
confidence: 82%
“…We and others have previously observed that cationic polymers and dendrimers can, under certain conditions, trigger bioluminescence in the marine bacterium V. harveyi , suggesting they may induce or enhance quorum sensing. 7 , 8 , 10 , 11 In a more recent study where we extended this work to the human pathogen V. cholerae , we observed that polymer-mediated clustering led to enhanced deposition of biomass and extracellular DNA, whereas it interfered with the induction of virulence genes in an infection model. 12 Because virulence and biofilm production are both regulated by quorum sensing but are usually both regulated concurrently, the goal of this study was to test whether cationic polymers would trigger quorum sensing in V. cholerae and how this would affect downstream transcription of biofilm genes.…”
Section: Discussionmentioning
confidence: 82%
“…Semisynthetic ammonium-terminated gallic acid-triethylene glycol Ds (GATG) developed by Leire et al (2016) have been shown to be able to interact with bacteria, thus attracting researchers as potential multivalent macromolecules for the development of new antimicrobials [ 98 ]. GATG Ds, due to the presence of primary amines in their periphery, were capable of sequestering bacteria cells and to induce the formation of clusters in Vibrio harveyi , an opportunistic marine luminescent pathogen.…”
Section: Cationic Antibacterial Dendrimers (Cads)mentioning
confidence: 99%
“…Finally, it would be of interest to evaluate the effects of functionality, charge, polymer/nanoparticle size and architecture systematically in bacterial recognition, biofilm penetration and therapeutic delivery. [46][47][48][49] It is well-established that natural nanoparticulates such as viruses can penetrate through many biological barriers, and biomimicry of bacteriophage structural features might in future allow development of highly active synthetic NPs which exhibit functional mimicry and anti-bacterial action also.…”
Section: D Skin Infection Modelmentioning
confidence: 99%